Pengaruh Model Pembelajaran Matematika Realistik terhadap Hasil Belajar Matematika bagi Siswa Sekolah Dasar - Lestari, Adisa Rara Ayu Dwi; Manurung, Alberth Supriyanto (Universitas Nusantara PGRI Kediri, 2024)
The learning model is a factor that can influence learning outcomes, so in order to achieve maximum learning outcomes, teachers must be able to select and define the appropriate learning model. The purpose of this study is to determine the effect of the realistic mathematics model on student learning outcomes. This research uses an experimental research design. The population of this study is all fifth-grade classes at SD Negeri Kembangan Utara 06 Pagi, with VA class as the control group and VB class as the experimental group. The research sample consists of 64 respondents. The learning outcomes test used is a multiple-choice pretest and posttest. The result of this research shows that there's implementation of realistic mathematics learning model has an influence on learning outcomes in mathematics. Based on the t-test analysis, the research findings show a significant effect of the realistic mathematics learning model on mathematics learning outcomes, therefore, the alternative hypothesis (H1) is accepted.